Education in the interests of Emir Abdelkader - draou, mohamed; laib, mamar (Journal of Social Sciences and Humanities, 2024)
This study presents one of the aspects of the cultural contribution of Emir Abdelkader, by highlighting the environment that embraces science, knowledge and genius at the Guetna Institute, which is supervised by his father. This scientific and cultural radiation removed the stereotype that the Maghreb had no civilization or culture, especially among Western and even Eastern historians. And investing this knowledge effort in establishing educational structures and innovative curricula for his country and not leaving it to individual initiatives only. And highlighting the shortcomings by not establishing the Arab Translators Authority warns it of the senior scholars imposed by the inevitability of confrontation war and peace with the French. And we have taken note of the manifestations of this educational message, which were translated by the Emir’s writings in poetry and prose, and in many of its turns, it showed an accurate scientific path, a renewal vision, and intellectual and civilized debates that preoccupied Muslims and Christians.